2020
DOI: 10.26773/mjssm.200305
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an In-Season 8-Week Plyometric Training Programme Followed By a Detraining Period on Explosive Skills in Competitive Junior Soccer Players

Abstract: The aim of this study was to examine the effect of an eight-week plyometric training and resistance programme, on different motor abilities, kicking speeds, and individual techniques in competitive junior soccer players. A training programme was applied for eight weeks and was composed of countermovement jump, countermovement onto a box, sprints, and sprints with change of direction. The players were evaluated in three moments: before the start of the training programme, after the application of the training p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 22 publications
1
22
0
2
Order By: Relevance
“…If we take into account the dynamics of its growth, we can say with certainty that it will soon be included in one of the three most prestigious categories within the "Web of Science" database (SCI, SSCI or SCIE) and will receive an impact factor. Very high quality scientific papers by eminent authors, which were published in the first [34, 35, 36, 37, 38, 39, 40, 41, 42, 43, ] and the second edition of the eight volume [44,45,46,47,48,49,50,51,52,53], and also in the first edition of the ninth volume [54,55,56,57,58,59,60,61,62,63,64]are guarantee that it will happen. At the very end, the youngest, but still a journal that has made notable progress is the "Journal of Anthropology of Sport and Physical Education".…”
Section: Discussionmentioning
confidence: 99%
“…If we take into account the dynamics of its growth, we can say with certainty that it will soon be included in one of the three most prestigious categories within the "Web of Science" database (SCI, SSCI or SCIE) and will receive an impact factor. Very high quality scientific papers by eminent authors, which were published in the first [34, 35, 36, 37, 38, 39, 40, 41, 42, 43, ] and the second edition of the eight volume [44,45,46,47,48,49,50,51,52,53], and also in the first edition of the ninth volume [54,55,56,57,58,59,60,61,62,63,64]are guarantee that it will happen. At the very end, the youngest, but still a journal that has made notable progress is the "Journal of Anthropology of Sport and Physical Education".…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no study analysed the effects of detraining on CODS in young soccer players, which means that future research is warranted. In a study that investigated the effects of an in-season plyometric training, followed by detraining on physical performance in junior male soccer players (~17 years), the authors observed that the ability to change of direction with ball during a dribbling speed test was not affected by a 4-week detraining period (Branquinho et al, 2020). Although these results may indicate that this quality can be preserved after the detraining, the findings are specific to the dribbling speed test.…”
Section: Change Of Direction Speed Testmentioning
confidence: 97%
“…Sportski trening kao sastavni dio trenažne tehnologije, omogućavaju transformacione procese pojedinih segmenata antropološkog statusa sportiste i usavršavanje tehničko-taktičkih elemenata, što u krajnjem vodi ka postizanju vrhunskih sportskih dostignuća. Iz ovog veoma važnog segmenta su prikazani sljedeći radovi: "Exponential versus linear tapering in junior elite soccer players: effects on physical match performance according to playing positions" (Krespi, Sporis, & Popovic, 2019), Neuromuscular adaptations after blood flow restriction training combined with nutritional supplementation: A preliminary study" (Chulvi-Medrano et al, 2019), "The Effects of High-Intensity Interval Training on Skeletal Muscle Morphological Changes and Denervation Gene Expression of Aged Rats" (Tayebi, Siahkouhian, Keshavarz, & Yousefi, 2019), "The Association between Relative Age Effect, Goals Scored, Shooting Effectiveness and the Player's Position, and her Team's Final Classification in International Level Women's Youth Handball" (Saavedra, & Saavedra, 2020), "The Effects of A 6-Week Plyometric Training Programme on Sand Versus Wooden Parquet Surfaces on the Physical Performance Parameters of Well-Trained Young Basketball Players" (Ozen, Atar, & Koc, 2020), "The Effect of an In-Season 8-Week Plyometric Training Programme Followed By a Detraining Period on Explosive Skills in Competitive Junior Soccer Players" (Branquinho et al, 2020), "Warm-Up Striding Under Load Does Not Improve 5-Km Time Trial Performance in Collegiate Cross-Country Runners" (O'Neal et al, 2020), "The influence of coaches' instruction on technical actions, tactical behaviour, and external workload in football small-sided games" (Batista et al, 2019), "The important game-related statistics for qualifying next rounds in Euroleague" (Dogan, & Ersoz, 2019) i "Normative Profile of the Efficacy and Way of Execution for the Block in Women's Volleyball from Under-14 to Elite Levels" (Echeverría, Ortega, & Palao, 2020).…”
Section: Total 30mentioning
confidence: 99%